(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The word „’ADOLESCENT’’ is derived from the Latin word “ADOLESCERE’’ which means to grow to maturity that indicated the detaining features of adolescence. Adolescents belong to vital age group because they are the important people to parenthood but also they are threshold between childhood and adulthood .As they are attempt to cross this threshold, they face various psychological and developmental changes